Tingkat Kepuasan Wali Murid terhadap Pelayanan Pelatih Klub Renang Science Swimming Team (SST) Sidoarjo - Mohammad Damang Prasetya; Made Pramono (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Children's education and development are crucial aspects and a primary concern for parents, especially in the field of sports. In this context, the Science Swimming Team (SST) Sidoarjo swimming club plays a strategic role in providing quality swimming training for children. This study aims to evaluate the level of parental satisfaction with the quality of services provided by the club's coaches. Using a quantitative approach and descriptive design, this study collected data through a closed-ended questionnaire distributed to 15 respondents who were parents of students at SST. The research instrument was structured based on five dimensions of service quality: tangibles, empathy, reliability, responsiveness, and assurance. The data obtained were then analyzed descriptively quantitatively by calculating frequency distributions and percentages to obtain a clear picture of the level of parental satisfaction. The results showed that the majority of respondents, namely 53.33%, felt quite satisfied with the services provided by the coaches, while 26.67% felt satisfied, 13.33% were less satisfied, and 6.67% were dissatisfied. The reliability and responsiveness dimensions scored highest, indicating that coaches were able to provide reliable and responsive services to parents' needs. However, the tangible and empathy dimensions still need to be improved to achieve optimal satisfaction. The implications of these findings suggest that coaches and club management need to strengthen the quality of existing facilities and infrastructure and develop a more empathetic communication approach with parents. This is crucial for creating a better relationship between coaches and parents, thereby increasing their trust and satisfaction with the services provided. Future research is recommended to expand the number of respondents and identify specific factors influencing satisfaction, so that the results obtained are more comprehensive and applicable in the context of service development in swimming clubs.